THE EFFECT OF BALL HANDING AND WALL VOLLEYBALL TRAINING ON SUMBAWA CLUB DOWN PASSING SKILLS IN 2023 - Bima Votum Ade Yasa; Subakti; Nurdin (Sinar Lima, 2024)
Focus of this research problem is that in lower passes there are lots of inappropriate passes, so that lower passes are felt to be inaccurate, the way to do them is wrong and mistakes often occur in making these lower passes. Research bbjectives to find out if there is a difference the effect of ball handing and wall volleyball training on Sumbawa Club's lower passing skills in 2023. The research design used was experimental research